Downton Abbey - Percival, Brian; Bolt, Ben, 1952-; Smith, Maggie, 1934-2024; Bonneville, Hugh; McGovern, Elizabeth, 1961- ([Alexandria, Va.] : PBS Distribution, 2011)
Follows the lives of the aristocratic Crawley family and their servants in pre-WWI England.
Features: Downton Abbey : a house in history, making-of featurette.
Maggie Smith, Hugh Bonneville, Elizabeth McGovern, Jim Carter, Phyllis Logan, Michelle Dockery, Dan Stevens.
Originally broadcast on television as a segment of the "Masterpiece classic" series of "Masterpiece theatre" in 2010.
TV rating: Not rated.
DVDs, Dolby digital stereo.
Closed-captioned.
Keywords: Aristocracy (Social class) -- England -- Drama; Country life -- England -- History -- 20th century -- Drama; Families -- England -- Drama; Household employees -- England -- Drama; Historical television programs; Video recordings for the hearing impaired; Fiction television programs